Effect of Fungicide Application Rate and Frequency on development of Major Faba bean Diseases, Grain Yield and Yield Components of Faba Bean (Vicia Faba L.) at Southeastern Oromia, Bale - Ermias Teshome Taffa; Dagne Kora Balcha (Open Journal of Plant Science - Peertechz Publications, 2022)
The experiment was conducted at Sinana and Agarfa to determine the application rate and frequency of MATICO. Randomized Complete Block Design with three replications was used to lay out the experiment. Logistic model (ln[y/ (1-y)]) was used to estimate r. Correlation and regression analysis were employed to find the relationship between diseases' severity, yield, and yield-related traits. Analysis of Variance (ANOVA) for diseases parameters has shown significant differences (p<0.05) between treatments. The highest diseases parameters were recorded from unsprayed and plots sprayed with lower rates and frequency and the lowest was recorded from plots sprayed four tines at 2.5 kg/ha. ANOVA for yield and yield-related traits has shown significant variations (P<0.05) among treatments. The highest pods per plant (21), thousand Kernel Weight (664.7g), and grain yield (3319.4kg/ha) were recorded from plots sprayed four times at 2.5 kg/ha. Simple linear regression has revealed a significant association (P<0.0001) between grain yield and diseases severity and the Correlation of grain yield with diseases severity has depicted a significant negative correlation. The highest marginal rate of return (2126.31%) was obtained from plots sprayed twice at 2.5kg/ha. Therefore, two times application of MATICO WP at a rate of 2.5 kg/ha is recommended.